Symbolic and cultural implications of phenomenon of body tattoo among the youth An anthropological study in city Lattakia - خرما ايفا (Latakia University Journal - Arts and Humanities Sciences Series, 2024)
The phenomenon of has spread in the Syrian society, and especially among youth generation and developing in manner that is compatible with mode and fashion, until the body became the means for expressing the opinions of its companions. THE MEANS FOR EXPRESSING THE OPINIONS OF ITS COMPANIONS. The phenomenon of tattoos is not modern or extraneous to the Iocal community, grandparents diditin it in the past. While the males choose to draw a snake, dragon, scorpion or or skull to express strength and stiffness, the girs draw a rose, butterfly or fish, while others who took the tattoo use a bond of love to write the name of the lover or draw his image on the body. And the spread of tattoos among the younger generation at the present time has become a process of imitating celebrities, incuding artists, athetes. Although religiions are clearly forbidden by this behavior, addition to the difficulty of removing a tattoo on the body due to the health risk associated with the removal process, we notice many young peoble accebting this act. This research is an attempt to understand the phenomenon of tattooing on the human body, and clarify its symbolic and cultural implications for the youth in Lattakia.